Physiopathology of splanchnic vasodilation in portal hypertension - Martell, María (Baishideng Publishing Group Co., Limited, 2010)
In liver cirrhosis, the circulatory hemodynamic alterations of portal hypertension significantly contribute to many of the clinical manifestations of the disease. In the physiopathology of this vascular alteration, mesenteric splanchnic vasodilation plays an essential role by initiating the hemodynamic process. Numerous studies performed in cirrhotic patients and animal models have shown that this splanchnic vasodilation is the result of an important increase in local and systemic vasodilators and the presence of a splanchnic vascular hyporesponsiveness to vasoconstrictors. Among the molecules and factors known to be potentially involved in this arterial vasodilation, nitric oxide seems to have a crucial role in the physiopathology of this vascular alteration. However, none of the wide variety of mediators can be described as solely responsible, since this phenomenon is multifactorial in origin. Moreover, angiogenesis and vascular remodeling processes also seem to play a role. Finally, the sympathetic nervous system is thought to be involved in the pathogenesis of the hyperdynamic circulation associated with portal hypertension, although the nature and extent of its role is not completely understood. In this review, we discuss the different mechanisms known to contribute to this complex phenomenon.